2020
DOI: 10.3389/fimmu.2020.01621
|View full text |Cite
|
Sign up to set email alerts
|

Non-ischemic Heart Preservation via Hypothermic Cardioplegic Perfusion Induces Immunodepletion of Donor Hearts Resulting in Diminished Graft Infiltration Following Transplantation

Abstract: Introduction: Many donor organs contain significant leukocyte reservoirs which upon transplantation activate recipient leukocytes to initiate acute rejection. We aimed to assess whether non-ischemic heart preservation via ex vivo perfusion promotes immunodepletion and alters the inflammatory status of the donor organ prior to transplantation. Methods: Isolated porcine hearts underwent ex vivo hypothermic, cardioplegic perfusion for 8 h. Leukocyte populations were quantified in left ventricle samples by flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Most immunosuppressive agents act at the T cell level [31] however, upstream pathways may also be targeted to reduce rejection. The link between oxygenated perfusion and immunomodulation has been shown in animal models for kidneys, [32] heart, [33] and liver, [34] providing oxygen during organ storage diminished the initial oxidative stress and DAMP molecule release, thus downregulating the entire immune activation cascade. Mitochondria have been shown to be an important therapeutic target to reduce acute rejection in other solid organs as well, such as hearts, [35] lungs, and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Most immunosuppressive agents act at the T cell level [31] however, upstream pathways may also be targeted to reduce rejection. The link between oxygenated perfusion and immunomodulation has been shown in animal models for kidneys, [32] heart, [33] and liver, [34] providing oxygen during organ storage diminished the initial oxidative stress and DAMP molecule release, thus downregulating the entire immune activation cascade. Mitochondria have been shown to be an important therapeutic target to reduce acute rejection in other solid organs as well, such as hearts, [35] lungs, and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this work, Michel and Madsen [38] reported that a NIHP porcine model resulted in hearts with less depletion of ATP stores and improved preservation of mitochondrial structure. Critchley et al [39] echoed the physiological benefits of NIHP -in this study, six Swedish pigs underwent heart retrieval. Three organs were preserved with SCS for 2 h and the remainder were preserved for 8 h with NIHP.…”
Section: Hypothermic Machine Perfusionmentioning
confidence: 82%
“…MP may reduce acute graft rejection. A porcine heart study showed that NIHP could significantly reduce donor heart immunogenicity via loss of resident leukocytes, reducing recipient T cell recruitment up to 48 h following transplantation in the absence of immunosuppression ( 47 ). No clinical study has addressed on this topic so far.…”
Section: Discussionmentioning
confidence: 99%